Strategi Usaha Restoran di Kawasan Pariwisata Lebih, Kabupaten Gianyar pada Era Adaptasi Kebiasaan Baru (Studi Kasus di Restoran Genius Café Vision dan Restoran Andrawina) - I Nyoman Arcana; I Nyoman Wiratnaya (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2021)
Since the COVID-19 global pandemic, consumer behavior in restaurants has changed. This study aimed to determine the impact of the COVID-19 pandemic on restaurant businesses in Lebih Tourism Area, Bali and to formulate a survival strategy for restaurant managers in the area during the new normal era. Data were collected by interviewing the manager of Genius Cafe Vision and the manager of the Andrawina Restaurant Gianyar. Andrawina Restaurant and Genius Café have designed a clear strategy to gain consumer trust, but during the Covid-19 pandemic, it is clear that differences in market segments significantly affect restaurant revenues. This study concluded that the COVID-19 Pandemic caused the restaurant industry in Lebih, Gianyar to experience a significant decrease in income. Restaurants that were still operating on a limited basis continued to adapt operationally by reducing types and variations of menus, implementing delivery service, reducing the opening hours, reducing maximum number of visitors, reducing the number of staff, lowering selling prices, reduction of food portion sizes, changing marketing strategies and implementing health protocols in the restaurants. This study found that the strategy used were